2008
DOI: 10.1128/aac.01671-07
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Cell-to-Cell Transmission of Human T-Cell Lymphotropic Virus Type 1 In Vitro by Carbohydrate-Binding Agents

Abstract: Peripheral blood mononuclear cells (PBMCs) from healthy individuals can be infected by human Tlymphotropic virus type 1 (HTLV-1) upon cocultivation of the PBMCs with irradiated HTLV-1-transformed human MT-2 cells. This model system closely mimics HTLV-1 transmission through cell-to-cell contact.Carbohydrate-binding agents (CBAs) such as the ␣(1,3)/␣(1,6)mannose-specific Hippeastrum hybrid agglutinin and the GlcNAc-specific Urtica dioica agglutinin, and also the small, nonpeptidic ␣(1,2)-mannose-specific antibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…Moreover, similar results were obtained by coculturing JETWT35 cells with MT-2 cells ( Fig. 4C), which is another donor cell line widely used for HTLV-1 infection (38)(39)(40)(41)(42)(43). Interestingly, this inhibition of HTLV-1 transmission by PPS became inefficient when PPS was added to the coculture 12 h later ( Fig.…”
supporting
confidence: 79%
See 1 more Smart Citation
“…Moreover, similar results were obtained by coculturing JETWT35 cells with MT-2 cells ( Fig. 4C), which is another donor cell line widely used for HTLV-1 infection (38)(39)(40)(41)(42)(43). Interestingly, this inhibition of HTLV-1 transmission by PPS became inefficient when PPS was added to the coculture 12 h later ( Fig.…”
supporting
confidence: 79%
“…To this end, we used human umbilical vascular endothelial cells (HUVEC) because they are primary cells that resemble BBB cells and can be infected by HTLV-1 (44,45). We used lethally irradiated MT-2 cells as the donor cells to infect HUVEC, which is a widely used method of HTLV-1 infection (38)(39)(40)(41)(42). We first confirmed that there were no viable MT-2 cells 3 days after lethal irradiation by a trypan blue exclusion assay (data not shown).…”
mentioning
confidence: 99%
“…However, it remains to be determined whether those lymphocytes circulate for longer in saliva or are newly deposited in saliva and milk by leaking from microcirculation as has been reported previously (32)(33)(34)(35). There is some indirect evidence, both from our own study and previous work for HTLV-1 infection of oral mucosa by cellto-cell contact with circulating T cells, primarily through breast-feeding (32,(36)(37)(38).…”
Section: Discussionmentioning
confidence: 64%
“…4 These CBAs are also active against infection of certain viruses of the Nidovirales family, like coronaviruses, 4,7,202 arteriviruses, and toroviruses, 8 and against CMV, 66 the feline immunodeficiency virus 203 and DENV 6 infection and cell-to-cell transmission of HTLV-1. 204 CV-N has also been found inhibitory to Ebola virus and influenza virus. 44,205 Conflicting reports, however, exist on the potential of CBAs to inhibit HSV entry.…”
Section: Effect Of Cbas On Other Pathogens Than Hivmentioning
confidence: 99%